Problems of Statistical Description of Crime Based on Police Statistics (Archives of Criminology, 2000)
Crime, like any other social phenomenon, requires a statistical description. That description has been changing together with changes of the criminological paradigms. Today, data from three different sources are use to measure crime: official statistics, self-report surveys, and victimization surveys. The data are difficult to compare (in respect of their type, extent, and manner in which they are acquired); however, they are complementary and permit a multi-dimensional description of the phenomenon. The oldest and still the basic source of figures on crime are the crime statistics. What has changed, however, is the approach to such data. Today, they are evaluated in three different perspectives: realistic, institutional, and radical. The present study signals the problems that arise when trying to provide a statistical description of crime of the 1990s basing on police statistics interpreted (to a varying extent) in all three perspectives. My point of departure is the assumption that just like the other statistics of crime, the police statistics is a social construct. It is a product of social, political and organizational processes. Explanation of the process of statistics-making help towards a qualitative evaluation of the data contained in the statistics. The data from police statistics may be treated as indices of both the functioning of the institutions for social control, and of detected crime that results from such control.Important in the social process of statistics-making is both the occurrence of specific events or behaviors and the social reaction to them. Possessing political power, the state creates the system of laws together with organizational structures that supervise the observance of those laws. The functioning of the formalized legal control may be analyzed from the viewpoint of decisions taken by the legislator in the process of law-making as well as those taken by institutions specially appointed to exercise such control. Fundamental in the process of making of police statistics is the role of decisions taken by the police in the course of prosecution. The police (as well as other prosecution agencies) is authorized by state authorities to detect, qualify, register and count events that are found to be offences and the perpetrators of those acts. It is authorized to gather, process and publish data.The legislative process, that is the legislator's decisions concerning law-making, may be appraised in various perspectives. Important in the context of interpretation of data from police statistics is their evaluation in the perspective of criminalization/de-criminalization and penalization/de-penalization acts, construction of substantive penal law and criminal procedure institution, as well as regulation of the structure and competencies of agencies dealing with public safety and order, the police included. Also monitored should be legislative "steps" in the area of misdemeanors law and penal law concerning offences against the Treasury.In the process of both formalized and informal social control, offences are "disclosed''; evcnts and behaviors idcntified with prohibited acts are distinguished from among the bulk of events and behaviors. To "disclose'' an offence, one needs knowledge as to what is and what is not a prohibited act; the opportunity to recognize that offence; and the awareness of recognizing it. In our system, the institutions appointed thus to "disclose'' offences include the Police, the prosecutor's office, the Office of State Protection, Military Police, Frontier Guards, fiscal inspection agencies, the Customs Inspection, State Sanitary Inspection, State Trade Inspection, as well as other agencies specified in individual laws. As can be supposed, most offences are disclosed by the victims, natural persons, and members of victimized institutions.Disclosure of an offence is not tantamount to its reporting. Self-report surveys confirm the existence of disclosed but unreported offences. As follows from such surveys, people in different countries show different tendencies to report facts of victimization to the police, and those tendencies depend on the type of offence involved. In Poland, it is the citizens' social duty to report offences; that duty becomes legal in exceptional situations and with respect to a specific group of offences only.Not all reported offences are registered. Registration follows strictly specified rules related to the system of information gathering and processing that is currently binding upon the prosecution agencies. Registration of offences proceeds through a prosecution agency's decision to institute preparatory proceedings. Most often, the proceedings are instituted on the citizens' initiative.Once instituted, preparatory proceedings aims at establishing whether a prohibited act has in fact been committed and whether that act constitutes an offence. The event with respect to which qualification of the act as an offence has been confirmed by completed preparatory proceedings is treated as an established offence in police statistics.Preparatory proceedings also aims at detecting the offender, that is at identifying the person who has in fact committed a given act. At the preparatory stage, this person is treated as the suspect. In most cases, identification of the suspect by the prosecution agencies bases on indication made by the person who reported the offence. The process of detection of offenders varies depending on the type of offence, indication or lack of indication of the suspect at the moment of reporting the offence, and the province in which the preparatory proceedings was conducted.The legislator authorized the Police not only to detect, qualify and register offences, to detect offenders, and to take a variety of decisions concerning acts and persons in preparatory proceedings (at the stage of its institution, course, and completion), but also to gather appropriate data about those acts and persons and then to count, process and publish such data.The term "police statistics'' usually means a collection, gathered and published by the Police, of figures pertaining to crime. Such figures make it possible to describe the quantitative aspect of the phenomenon, but may be quite misleading if used in a wrong manner. Data from police statistics may be used mechanically, so to say, simply quoted with no attempt at explanation. They may be manipulated, that is used in a biased way towards specific aims. As we know, figures can be used to prove any hypothesis whatever, provided that they are selected, put in order, confronted and counted. They can also be interpreted; this, however, is where difficulties start to arise. It appears that it is by no means a simple task to provide a statistical description of crime basing on police statistics. The picture of crime that emerges from that statistics is usually described in a language typical of interpretation of such data in the realistic perspective. We speak of the extent of crime, its dynamics, and trends as if we believed that the data gathered by the Police permitted characterization of "real crime". Despite this language of the realistic perspective, the actual analysis bases on all three perspectives, that is also on the institutional and the radical one. This means that using police stirtistics, we at the same time analyze the process of their making. Awareness of the process in which the data emerge determines the manner of describing and interpretation of the phenomenon of crime.